The Relationship Between Employee Job Stress and Employee Performance - Anne Lasminingrat (DINASTI RESEARCH, 2021)
With the many problems that occur in the company where the researcher works, the researcher is interested in conducting this research. This study aims to determine the relationship between employee job stress and employee performance. The method used is a quantitative method. Samples were taken as many as 35 people. The data collection technique of this research used a questionnaire and literature study. Analysis of the data used is simple linear regression analysis. The results of the analysis obtained the equation Y = 36,778 +-, 345 X. Hypothesis testing using the t test, which shows that the work conflict variable has a negative and significant effect on employee performance. The conclusion of this study is that there is a negative and significant relationship between work stress and employee performance , meaning that the higher the work stress , the lower the employee 's work performance.